Adonis to Zorro Oxford dictionary of reference and allusion - Delahunty, Andrew; Dignen, Sheila; Oxford eBooks ([Oxford] : Oxford University Press, 2010)
This dictionary explains the meanings of references and allusions that are likely to be encountered in modern English. Drawing on the resources of the Oxford English Corpus, illustrative examples are provided for almost every entry. Fully cross-referenced and with a thematic index, it is ideal for browsing or quick reference.
"Oxford Reference Online Premium."
Title from title page (viewed on Aug. 27, 2010).
Also issued in print format.
Keywords: Allusions -- Dictionaries; Electronic books